Reliability, validity and normal ranges of the Zur Balance Scale for detecting mild postural control differences: introducing the modified, short version mZBS - Zur, Oz; Ben-Rubi Shimron, Hadas; Deutsch, Lisa; Carmeli, Eli (Frontiers in Human Neuroscience, 2023)
Introduction: Balance is achieved through interactions between the vestibular, somatosensory and visual systems. There are several clinical tests to measure postural stability. However, most of them do not assess postural stability with head movements, which is the main function of the vestibular system, and those that do, require the use of sizeable, expensive equipment. Therefore, an applicable, easy-to-perform test that challenges the function of the visual, somatosensorial and vestibular systems, using head movements, is needed. The Zur Balance Scale (ZBS) contains ten conditions, which are a combination of surfaces (floor or Styrofoam with subject standing on its width in Romberg position or its length in tandem position), stances (Romberg or tandem), tasks (no head movement with eyes open or closed and horizontal or vertical head movements with eyes open). The purpose of this study was to determine the validity, inter- and intra-examiner reliability, and normal performance values of the ZBS among individuals 29–70-years of age and to introduce the modified version: the mZBS, using kinetic measurements. Methods: Healthy participants ages 29-70 years were evaluated for inter- and intra-tester reliability (n=65), kinetic measurements on a force plate, and validity compared to the modified clinical test of sensory interaction and balance (mCTSIB) (n=44) and characterization of normal values (n=251). Results: ZBS head movements, duration of each condition (up to 10 seconds) and the total ZBS score were in agreement across examiners (ICC >0.8). Normal ZBS scores were significantly lower after age 60 years compared with younger subjects (P<0.0001). Older subjects (60–70 years) had a median score of 95.5 compared with younger subjects, where medians ranged from 97.6 to 98.9. Kinetic parameters showed positive correlations between ZBS and the mCTSIB scores, with the highest correlation between the five Romberg tasks (modified ZBS). Conclusion: ZBS is a valid and reliable test. Its advantages include using head movements and the ability to detect minimal differences in postural control, even in healthy populations. Kinetic evaluation of the ZBS enables the use of a modified, shorter version of the ZBS (mZBS).